Some Reflections About the Famine of Turkestan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, during the reign of Tsarist Russia in the territory of Turkestan, the cotton harvest replaced all agricultural crops, the country's economy turned into a raw material base for Russian industry, which caused huge losses per capita as a result of various historical events. sources. In particular, there is information that in 1917, due to the outbreak of the civil war in Russia, the import of grain from Russian provinces to Turkestan was stopped, and a significant part of the population died of starvation due to famine. shortage of grain in the country.